HYBRID VEHICLE CONTROL SYSTEM - Dvadnenko, V.; Двадненко, В. Я. (Харьковский национальный автомобильно-дорожный университет, 2016)
The hybrid vehicle control system includes a start–stop system for an internal combustion en-gine. The system works in a hybrid mode and normal vehicle operation. To simplify the start–stop system, there were user new possibilities of a hybrid car, which appeared after the conversion. Results of the circuit design of the proposed system of basic blocks are analyzed.
СИСТЕМА УПРАВЛЕНИЯ КОНВЕРСИОННОГО ГИБРИДНОГО АВТОМОБИЛЯ
СИСТЕМА КЕРУВАННЯ КОНВЕРСІЙНОГО ГІБРИДНОГО АВТОМОБІЛЯ
Keywords: BLDC motor; conversion of the vehicle; drive; system start–stop; hybrid vehicles; вентильный электродвигатель; конверсия автомобиля; электропривод; система старт–стоп; гибридный автомобиль; 621.313.333